Dukungan Keluarga dalam Meningkatkan Kesejahteraan Anak-Anak di Sanggar Anak Sungai Deli dengan Peran Keluarga, Pendidikan, dan Lingkungan Sosial - Saskia A. Hasibuan; Berlianti Berlianti (Concept: Journal of Social Humanities and Education, 2025)
The family plays a central role in shaping children’s growth and well-being, particularly in marginalized communities where access to education and healthcare is limited. This study aims to describe the forms of family support in improving the well-being of children at Sanggar Anak Sungai Deli, a non-formal educational institution located along the banks of the Deli River in Medan City. Using a qualitative descriptive approach, the research involved observations, in-depth interviews, and documentation. The informants included families of children, sanggar administrators, and children actively participating in the program. The findings reveal that family support is manifested in six main indicators: (1) positive emotional relationships, (2) provision of safety and comfort, (3) instilling positive values, (4) support for education and talent development, (5) protection from negative influences, and (6) partial fulfillment of basic needs. These supports contribute significantly to children’s emotional, social, and intellectual well-being, although the physical aspect remains less fulfilled due to economic constraints. Despite limited financial resources, families demonstrate care and commitment to supporting their children’s development. Sanggar Anak Sungai Deli serves as an essential partner by providing a safe and supportive learning environment. This study concludes that family involvement, combined with community-based interventions such as SASUDE, is crucial in ensuring holistic child well-being. The implications highlight the importance of strengthening collaboration between families, community organizations, and government to address gaps in child welfare programs in marginalized areas.